Magnetic resonance spectroscopy: A promising tool for the diagnostics of human prostate cancer?() - Kurth, Johannes (Urol Oncol, 2011)
BACKGROUND: Prostate Cancer (CaP) is one of the topmost diagnosed malignant diseases worldwide. In developed countries, early cancer detection methods have led to an increase of incidence rates over the last decades; however, with great variance of the prognosis. There is no diagnostic tool for an exact prediction of tumor aggressiveness, thus there is a lack of adequate and optimal treatment planning. METHODS: Electronic databases (Medline, PubMed) were scanned for scientific literature. Basic concepts of magnetic resonance spectroscopy (MRS), important results and its clinical applications were extracted and reviewed in this article. CONCLUSIONS: MRS provides crucial information about the metabolic status of human prostate samples while preserving the specimens for further investigations. Single metabolites and metabolomic profiles can be quantified to distinguish benign from malignant tissue and to predict aggressiveness, such as the recurrence rates of CaP. Studies are also anticipating that MRS might be beneficially applicable for in vivo investigations in the future.